The Influence of Product Quality, Price and Digital Marketing on Purchasing Decisions for Android Smartphones in The City of Denpasar - Ni Kadek lisa Pebrianti; A.A Ngurah Bagus Aristayudha; Kadek Riyan Putra Richadinata (Westscience Press, 2024)
A smartphone or smartphone being present in the environment. Due to the fact that it facilitates communication and provides instant access to information, this gadget has gained a dominant position in the worldwide electronics market. The purpose of this study is to investigate the following factors: the impact of product quality on decisions to purchase Android smartphones; the influence of price on decisions to purchase; and the impact of quality, price, and digital marketing on decisions to purchase Samsung smartphones. Quantitative surveying is the method that this research use. In Denpasar City, the population that was researched consisted of consumers that either use or purchase Android cellphones. The total sample size of 97 individuals was gathered through the employment of a purposive sampling approach, and the method of data collection was accomplished through the utilization of a questionnaire that had been validated and determined to be trustworthy. For the purpose of data analysis, multiple regression was utilized. The findings of the study indicate that the following factors have a significant impact on purchasing decisions: (1) the quality of the product has a significant impact on purchasing decisions; (2) the price has a significant impact on purchasing decisions; and (3) digital marketing and product quality have a powerful impact on purchasing decisions. The findings of the descriptive test on purchasing decisions obtained a total score of 415.6, with the second largest indicator (419) earning an average score of 4.28 and the smallest indication (412) obtaining the lowest score. The results of the descriptive test on product quality have a total score of 401, with an average score of 4.13 on the third largest indicator (414), which is the smallest 394. Total score for the price descriptive test was 401.6, with an average score of 4.14 on indications 2 and 3, with the maximum score being 403 and the smallest score being 399. There was a total score of 398.6 on the descriptive test for digital marketing, with an average score of 4.10 on indication 3, with the greatest being 413 and the smallest being 386.